Living with resource booms and busts: Employment scenarios and resilience to unconventional gas cyclical effects in Australia. (October 2019) - Measham, Thomas G.; Walton, Andrea; Graham, Paul; Fleming-Muñoz, David A.
Abstract: Recent research on unconventional oil and gas development (UOGD) proposes differences compared with established extraction of conventional energy, including the rise of shorter cycles of mini booms and busts. This paper builds on recent UOGD research discussing mini-booms/busts of the industry and considers factors affecting resilience of local businesses to cyclical effects using a case study of coalbed methane (coal seam gas) in Australia. The paper takes a mixed methods approach, combining qualitative interviews with local business communities and econometric modelling to quantitatively forecast potential changes in indirect employment under different scenarios for the period 2014–2034. The quantitative results demonstrate that, across all scenarios, employment rises in the sort to medium term then declines in the longer term. The scenario with the best economic resilience (long-term employment outcomes) involved decreasing dependence on the gas industry over time. The qualitative results show that experiences of local businesses did not readily align either to traditional long boom/bust nor the shorter periods of mini-booms and mini-busts, and many struggled to manage cyclical effects. In particular, local businesses had difficulty when an unforeseen lull in industry activity stretched out for several months before drilling eventually resumed. Taken combined, the qualitative and quantitative results indicate that the 'bust' part of UOGD is very much alive and may have been underestimated in recent literature. The findings emphasise that to manage unpredictable cyclical effects, there is a need for businesses to be flexible while retaining coping mechanisms for unforeseen circumstances. We conclude that economic effects of UOGD can vary considerably, noting that timing plays an important role as to how industry cycles play out and whether busts are relatively small corrections that can be absorbed by local economies or whether they are outside the realms of local resilience. We also draw attention to the role of intermediaries who play a critical role in providing trusted advice at a time of information overload and conflicting perspectives. We emphasise the need for policies to encourage economic resilience, based on diversification and assistance to local businesses to increase their adaptive resilience towards fluctuating periods of prosperity and recession.